Design, synthesis, and biological evaluation of novel 2′-deoxy-2′-fluoro-2′-C-methyl 8-azanebularine derivatives as potent anti-HBV agents. Issue 11 (1st June 2019) - Yang, Wu; Peng, Youmei; Wang, Jingwen; Song, Chuanjun; Yu, Wenquan; Zhou, Yubing; Jiang, Jinhua; Wang, Qingduan; Wu, Jie; Chang, Junbiao
Graphical abstract: This work describes the synthesis of new 2′-fluoro-2′- C -methyl 8-azanebularine nucleoside derivatives with moderate to good in vitro anti-HBV activity.2g can efficiently inhibit the wild-type and lamivudine-resistant HBV DNA replication. Abstract: Hepatitis B virus (HBV) is a global health problem requiring more efficient and better tolerated anti-HBV agent. In this paper, a series of novel 2′-deoxy-2′-fluoro-2′- C -methyl-β-d -arabinofuranosyl 8-azanebularine analogues (1 and2a) and N 4 -substituted 8-azaadenosine derivatives(2b-g) were designed, synthesized and screened for in vitro anti-HBV activity. Two concise and practical synthetic routes were developed toward the structural motif construction of 2′-deoxy-2′-fluoro-2′- C -methyl-β-d -arabinofuranosyl 8-azainosine from the ribonolactone3 under mild conditions. The in vitro anti-HBV screening results showed that these 8-azanebularine analogues had a significant inhibitory effect on the expression of HBV antigens and HBV DNA at a concentration of 20 μM. Among them, halogen-substituted 8-azaadenosine derivative2g displayed activities comparable to that of 3TC. In particular, 2g retained excellent activity against lamivudine-resistant HBV mutants.